An Analysis of Gender Identity Recognition in Court rulings on the merits (2015-2024) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The objective of this study is to examine the evolution of Italian Court rulings on the merits regarding the recognition of gender identity in the decade from 2015 to 2024. The analysis concentrates on the application by trial judges of the interpretive principles established by the Court of Cassation and the Constitutional Court concerning the mandatory requirement for sex reassignment surgery and the continuity of affective relationships. Moreover, the study analyses rulings on issues not expressly covered by Law 164/1982, including the choice of name and the issue of minors’ access to the proceeding. The objective is to demonstrate the alignment of lower court jurisprudence with the guidance provided by the higher courts and its contribution in addressing any interpretive gaps, thereby enhancing the protection of the fundamental rights of transgender individuals.
Keywords: Gender identity; Court rulings on the merits; trans; legal gender identity recognition; fundamental rights